Fluorescence imaging in vivo: recent advances - Rao, Jianghong; Dragulescu-Andrasi, Anca; Yao, Hequan (Current opinion in biotechnology, 2007)
In vivo fluorescence imaging uses a sensitive camera to detect fluorescence emission from fluorophores in whole-body living small animals. To overcome the photon attenuation in living tissue, fluorophores with long emission at the near-infrared (NIR) region are generally preferred, including widely used small indocarbocyanine dyes. The list of NIR probes continues to grow with the recent addition of fluorescent organic, inorganic and biological nanoparticles. Recent advances in imaging strategies and reporter techniques for in vivo fluorescence imaging include novel approaches to improve the specificity and affinity of the probes and to modulate and amplify the signal at target sites for enhanced sensitivity. Further emerging developments are aiming to achieve high-resolution, multimodality and lifetime-based in vivo fluorescence imaging.